System accuracy evaluation of the new blood glucose monitoring meter “GLUCOCARD S onyx” beyond ISO 15197:2013/EN ISO 15197:2015 requirements and with new patient safety features - Daisuke Azuma; Hisashi Okuda; Beate Saeger (Frontiers in Clinical Diabetes and Healthcare)
IntroductionBlood glucose monitoring meters (BGM) have not become redundant yet. The accuracy and precision of “GLUCOCARD S onyx,” a new BGM with Bluetooth function, has been evaluated and proven to exceed the actual ISO 15197:2013/EN ISO 15197:2015 guidelines besides offering features for better patient safety and telemedicine.Methods100 finger-prick whole blood samples from subjects with diabetes and 32 without diabetes were collected and measured with GLUCOCARD S onyx. Plasma blood glucose levels were measured using YSI2300 STAT PLUS as reference analyzer for comparison. The evaluation followed ISO 15197:2013, section 6.3 accuracy criteria. Furthermore, the MARD factor was calculated for the overall clinical important range (with n=132 samples).ResultsThe performance of GLUCOCARD S onyx was evaluated according to ISO 15197:2013, revealing that 99.7% (598/600) of the results fell within ±15% or ±0.8 mmol/L (± 15 mg/dL) of difference over the total clinically relevant glucose range compared to the YSI2300 STAT PLUS. 100% (600/600) of the measurement results over the total range fell within Clark Error Grid Zone A. An overall mean absolute relative difference (MARD) factor of 4.15% was obtained; 5.05% for glucose <5.6 mmol/L (<100 mg/dL), and 3.65% for glucose ≥5.6 mmol/L (≥100 mg/dL).DiscussionGLUCOCARD S onyx shows clinically satisfactory accuracy and reliability, even exceeding the ISO 15197:2013 criteria, for hypoglycemic cases with glucose critically low as <3.9 mmol/L (<70 mg/dL) and hyperglycemic cases with glucose ≥10.0 mmol/L (≥180 mg/dL). Healthcare organizations as well as manufacturers are aiming to offer new BGM systems that go beyond the ISO criteria and offer systems that can be consulted instead or besides CGM (Continuous Glucose Monitoring) in case of e.g. severe hypo- and/or hyperglycemic episodes. A MARD factor of 4.15% revealed an excellent system accuracy over the total clinically relevant glucose range. With additional user-friendly features, this BGM can be seen as a useful tool for efficient diabetes therapy, especially in the event of severe blood glucose fluctuations.